Coupled hydro-mechanical modelling on hydraulic fracturing using DDA. Issue 3 (October 2021) - Nie, Wen; Li, Shimeng; Yong, Zhaorui; Zhao, Zhiye
Abstract: Hydraulic fracturing is often used to increase the permeability of tight reservoir rocks. In this paper, a coupled hydro-mechanical module has been developed and coded into the Discontinuous Deformation Analysis (DDA) program to simulate the hydraulic fracturing progress. The governing equations of the couple hydro-mechanical module were introduced in the DDA framework. Parametric studies were conducted to investigate the effects of the sub-block sizes, sub-block shapes and strength heterogeneity on the development of the hydraulic fractures. It was found that bi-wing fracture was induced due to the increase of injection pressure and its orientation is approximately perpendicular to the direction of the minor principal stress. The increase of sub-block numbers could increase the simulated breakdown pressure. The simulations using quadrilateral sub-blocks would slightly increase the scales of the breakdown pressures compared with the triangular sub-blocks.